The Story of Doctor Dolittle. - Lofting, Hugh, 1886-1947 (First Avenue classics., 2017)
Dr. John Dolittle has always understood animals better than people. And when his parrot, Polynesia, teaches him the language of the animals, he really understands them. Dolittle opens up a veterinary practice in the quiet English village of Puddleby-on-the-Marsh and devotes his life to helping his furry, scaly, and feathered friends. His household menagerie includes Chee-Chee the monkey, Gub-Gub the baby pig, and Jip the dog. Together, the Doctor and his animal companions travel to the wilds of Africa to cure an epidemic that is plaguing the monkeys. There they meet African royalty, find actual canaries among the Canary Islands, and discover the legendary pushmi-pullyu. First published in 1920, this is an unabridged version of British author Hugh Lofting's fantastical adventure for animal lovers, which he both wrote and illustrated.